Adverse cosmetic reactions among Malaysian - Ai, Nur'ain; Zamli, Mazlina; Awadh, Ammar Ihsan JawaD; Ab. Hadi, Hazrina (2015)
Although the occurrence of adverse cosmetic reaction is often underestimate by the consumers; the incident of more severe reaction has been identified recently. The incident of adverse cosmetic reaction cannot be minimized or prevented by the regulations. However, the documentation of the incident might be helpful for the authority in regulating the cosmetic products. The aim of this study was to assess the prevalence, type of adverse cosmetic events and the measures adopted by those experiencing the adverse cosmetic events. To this aim, a SurveyMonkey questionnaire comprised of two sections: (a) demographic profile, (b) adverse cosmetic reaction was distributed to 552 consumers in Malaysia by snowball sampling method from April to June 2015. Statistical Package for Social Sciences (SPSS) version 20 was used to analyze the data. The result of this study revealed that 29% (n= 160) of total respondents experienced adverse cosmetic events with eczema as the most frequent type of adverse cosmetic event. Facial area (n=178) was mostly affected in the consequences of the usage of the products that are intended to be applied to the face area. After the incidents, 67 (41.1%) of the respondents choose to seek for professional consultation and majority of them prefer to simply change to other products. In conclusion, the prevalence, type of adverse cosmetic events and the measures adopted were documented and consumers are found to underestimate the incident of adverse cosmetic reactions. More reliable cosmetovigilance system may be applied to the population to increase their awareness on this matter.